2012
DOI: 10.1016/j.taap.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

An ethanolic extract of black cohosh causes hematological changes but not estrogenic effects in female rodents

Abstract: Black cohosh rhizome (Actaea racemosa) is used as a remedy for pain and gynecological ailments; modern preparations are commonly sold as ethanolic extracts available as dietary supplements. Black cohosh was nominated to the National Toxicology Program (NTP) for toxicity testing due to its widespread use and lack of safety data. Several commercially available black cohosh extracts (BCE) were characterized by the NTP, and one with chemical composition closest to formulations available to consumers was used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(67 citation statements)
references
References 37 publications
3
63
1
Order By: Relevance
“…In addition, BCE preparations are variable natural mixtures of compounds and it is not known which of these compounds are active. The mice in the current study were dosed relatively high at 1000 mg/kg; however, hematological effects were observed as low as 62.5 mg/kg (low-dose group) in the subchronic study (Mercado-Feliciano et al 2012). In addition, similar CBC changes were observed in the NTP subchronic rat BCE study (Mercado-Feliciano et al 2012).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, BCE preparations are variable natural mixtures of compounds and it is not known which of these compounds are active. The mice in the current study were dosed relatively high at 1000 mg/kg; however, hematological effects were observed as low as 62.5 mg/kg (low-dose group) in the subchronic study (Mercado-Feliciano et al 2012). In addition, similar CBC changes were observed in the NTP subchronic rat BCE study (Mercado-Feliciano et al 2012).…”
Section: Discussionmentioning
confidence: 74%
“…The mice in the current study were dosed relatively high at 1000 mg/kg; however, hematological effects were observed as low as 62.5 mg/kg (low-dose group) in the subchronic study (Mercado-Feliciano et al 2012). In addition, similar CBC changes were observed in the NTP subchronic rat BCE study (Mercado-Feliciano et al 2012). The typical recommended daily dose of BCE for humans is 40 mg daily, which is approximately 0.5mg/kg for a 70kg person.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Understanding its molecular mechanism(s) of action is, however, a conditio sine qua non for considering potential beneficial and unwanted side effects. The initially suggested estrogenic activity of lipophilic components, such as triterpenoids, was disproved by later studies (Gaube et al, 2007;Mercado-Feliciano et al, 2012;Hajirahimkhan et al, 2013). There, however, is evidence that A. racemosa L. preparations interact with distinct neurotransmitter systems in the central nervous system, including m-opioid receptors (Rhyu et al, 2006;Reame et al, 2008), serotonin (5-HT) receptors (subtypes 5-HT 1A , 5-HT 1D , and 5-HT 7 ) (Burdette et al, 2003), and dopamine subtype 2 receptors (Jarry et al, 2003).…”
Section: Discussionmentioning
confidence: 99%